PHENOTYPIC AND GENOTYPIC DETECTION OF METHICILLIN-RESISTANT Staphylococcus aureus (MRSA) ISOLATED FROM LOCAL AND IMPORTED MEAT SOLD IN BAGHDAD CITY.: PHENOTYPIC AND GENOTYPIC DETECTION OF METHICILLIN-RESISTANT Staphylococcus aureus (MRSA) ISOLATED FROM LOCAL AND IMPORTED MEAT SOLD IN BAGHDAD CITY. (Iraqi Journal of Market Research and Consumer Protection, 2026)
This study aimed to Isolation and identification with molecular detection of Methicillin-resistant Staphylococcus aureus (MRSA) isolated from imported (frozen) and local (fresh) meat using selective media, biochemical tests, VITECK 2 technology, and conventional PCR with sequencing. (100) meat samples were collected from different markets in Baghdad city, (50) samples from each local and imported meat. The results of cultural isolation from frozen meat reported (4/50) 8% as MRSA isolates, while, only (3/50) 6% of MRSA isolates were isolated from the fresh meat samples. All suspected isolates of Methicillin-resistant Staphylococcus aureus (MRSA) were positive for VITEK 2 system. The results of PCR assay of (7) positive isolates from both of local and imported meat samples shown 100% (7/7) for nuc and mecA gene, 71.42% (5/7) for possessed PVL gene and 6/7 (85.71%) for spa gene. The results of current study concluded that both two types of meat sold in local markets were contaminated with this dangerous pathogenic and the imported meat showed higher contamination rate with (MRSA) than the local fresh meat.